Art expertise modulates the emotional response to modern art, especially abstract: an ERP investigation - Else, Jane E.; Ellis, Jason; Orme, Elizabeth (Frontiers in Human Neuroscience, 2015)
Art is one of life’s great joys, whether it is beautiful, ugly, sublime or shocking. Aesthetic responses to visual art involve sensory, cognitive and visceral processes. Neuroimaging studies have yielded a wealth of information regarding aesthetic appreciation and beauty using visual art as stimuli, but few have considered the effect of expertise on visual and visceral responses. To study the time course of visual, cognitive and emotional processes in response to visual art we investigated the event-related potentials (ERPs) elicited whilst viewing and rating the visceral affect of three categories of visual art. Two groups, artists and non-artists viewed representational, abstract and indeterminate twentieth century art. Early components, particularly the N1, related to attention and effort, and the P2, linked to higher order visual processing, was enhanced for artists when compared to non-artists. This effect was present for all types of art, but further enhanced for abstract art, which was rated as having lowest visceral affect by the non-artists. The later, slow wave processes (500-1000ms), associated with arousal and sustained attention, also show clear differences between the two groups in response to both type of art and visceral affect. Abstract art increased arousal and sustained attention in artists, whilst it decreased in non-artists. These results suggest that aesthetic response to visual art is affected by both expertise and semantic content.